SEMIOTICS ANALYSIS LOGO OF STKIP SILIWANGI AND IKIP SILIWANGI - Ilviani Nurfatwa; Muthia Nur Alivah; Ula Nisa El Fauziah (PROJECT (Professional Journal of English Education), 2018)
Logo is symbols as identity an institution. Logo defines as the symbols which is distinguish one brand or institution with other institution. This study aimed to analyze the semiotics from logos of STKIP Siliwangi and IKIP Siliwangi. The purpose of study is to find the meaning of  two logos the college. The theory semiotics that used in this study is from Barthes’ theory. The theory is focused on analyzing the sign of denotative, conotative and myth meaning. The sign which analyzed are the shape, the color, and the font from the logos. In achieving the study, the writers used descriptive qualitative as the method of research. The finding of the study is the meaning of logo STKIP and IKIP Siliwangi which indicate from the value of Pancasila and value of Siliwangi. Keywords: Semiotics, sign, logos